A simple analysis of the U.S. emission permits auctions - Kline, Jeffrey J. (2015)
We examine a stylized version of EPA auctions when agents know the list of values of sellers and buyers. Sellers and buyers behave strategically. We show that there are two types of equilibria: inefficient equilibria where no goods are traded and efficient equilibria where alI exchange occurs at a uniform price. We also provide examples of the EPA auction game under incomplete information when the uniform price equilibrium holds and when it does not hold. When the uniform price equilibrium holds, sellers shade their bids up and buyers shade their bids down. In the example where the uniform price equilibrium does not hold, both buyers and sellers shade their bids down in an equilibrium.